Performance Comparison of PV Module Configurations in a Fixed-Load P2H System Considering Regional and Seasonal Solar Irradiance in Korea - Cheol-Woong Choi; Kuk-Tai Chang; Gi-Tae Park; Seung-Hoon Lee; Su-Youn Jeong; Yun-Soo Kang; Jae-Sub Ko; Dae-Kyong Kim (Energies)
This study investigates the impact of photovoltaic (PV) module configurations on the output performance of power-to-heat (P2H) systems under fixed-load conditions, considering regional solar irradiance characteristics in South Korea. Through both simulations and experimental analyses using a P2H testbed, two configurations, namely 6S (6Series) and 3S2P (3Series-2Parallel), were compared under varying irradiance levels. Based on an irradiance threshold of 533.2 W/m2, an adaptive PV configuration method is proposed to optimize energy output. The performance of the resistive-heating-based P2H system was evaluated using solar radiation data from major regions of Korea. Experimental results demonstrated that this approach can increase output power by up to 65% at low irradiance and improve annual energy yield by about 16% compared with a fixed configuration. This study offers practical guidance for designing P2H systems tailored to the climatic conditions in Korea.